Role Models of Aging among Older Men: Strategies for Facilitating Change and Implications for Health Promotion - Jordan Deneau; Rylee A. Dionigi; Paula M. van Wyk; Sean Horton (MDPI AG, 2023)
Understanding later-life role model choice and motivations, particularly for older men in sport, exercise, and health contexts, is complex and heterogenous, making it difficult for health and exercise promotion initiatives. This qualitative study examined: (1) whether older men have aging role models, and if so, their characteristics; and (2) older men's reasons for role model choice, or lack thereof, and how role models can influence meaningful change in perceptions and practices associated with aging, sport, exercise, and health. Through in-depth interviews and photo-elicitation with 19 Canadian men aged 75 years and over, thematic analysis determined two key themes: Role model choice, and Processes of role models facilitating change. Four key strategies for role models facilitating change in older men were determined: elite (biomedical) transcendence; valued exemplary endeavours; alliance connections; and disconnect and caveats. Ultimately, while promoting the biomedical achievements of role models may resonate with many older men, when applied too closely in sport or exercise contexts (e.g., using Masters athletes as role models), there is potential for unrealistic standards and overmedicalization that could miss uncovering the latent importance that older men place on the diverse experiences and perspectives of aging that go beyond traditional masculine ideals.